2014
DOI: 10.1111/tpj.12618
|View full text |Cite
|
Sign up to set email alerts
|

Systems approach identifies TGA1 and TGA4 transcription factors as important regulatory components of the nitrate response of Arabidopsis thaliana roots

Abstract: SUMMARYNitrate acts as a potent signal to control global gene expression in Arabidopsis. Using an integrative bioinformatics approach we identified TGA1 and TGA4 as putative regulatory factors that mediate nitrate responses in Arabidopsis roots. We showed that both TGA1 and TGA4 mRNAs accumulate strongly after nitrate treatments in roots. Global gene expression analysis revealed 97% of the genes with altered expression in tga1 tga4 double mutant plants respond to nitrate treatments, indicating that these trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
294
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(309 citation statements)
references
References 60 publications
15
294
0
Order By: Relevance
“…These eight TFs interacted with PYL6, a member of the recently identified PYR/PYL/ RCAR ABA receptor family (37)(38)(39)(40). Consistent with previous observations (41,42), the TF-NAPPA network also revealed molecular links between the ABA and nitrate signaling pathways via ARR14 and TGA1, which have been found to regulate nitrate response (43), although the molecular mechanism of this connection remains unclear. Our TF-NAPPA network provides a hypothesis that ABA and nitrate signaling cross-regulation occurs through protein-protein interactions between PYL6 and TGA1, and also suggests an interaction of the ABA signaling pathway with other plant hormones such as brassinosteroid (BZR1) or jasmonic acid (MYC2).…”
Section: Halotag-nappa Reveals a Potential Role Of Tfs In Plant Hormonesupporting
confidence: 71%
“…These eight TFs interacted with PYL6, a member of the recently identified PYR/PYL/ RCAR ABA receptor family (37)(38)(39)(40). Consistent with previous observations (41,42), the TF-NAPPA network also revealed molecular links between the ABA and nitrate signaling pathways via ARR14 and TGA1, which have been found to regulate nitrate response (43), although the molecular mechanism of this connection remains unclear. Our TF-NAPPA network provides a hypothesis that ABA and nitrate signaling cross-regulation occurs through protein-protein interactions between PYL6 and TGA1, and also suggests an interaction of the ABA signaling pathway with other plant hormones such as brassinosteroid (BZR1) or jasmonic acid (MYC2).…”
Section: Halotag-nappa Reveals a Potential Role Of Tfs In Plant Hormonesupporting
confidence: 71%
“…Nevertheless, it has not been tested if this phenotype can be recovered after nitrogen depletion for these mutants. On the contrary, nlp7, tga1/tga4, and lbd37/38/39 mutants have been analyzed after nitrogen starvation and the results showed inhibited induction of nitrate-responsive genes in nlp7 and tga1/tga4 mutants but higher induction in lbd37/38/39 mutants after nitrate treatments (Castaings et al, 2009;Rubin et al, 2009;Alvarez et al, 2014). However, the expression of nitrate-induced genes in these mutants has not been investigated without nitrogen starvation to date.…”
Section: Discussionmentioning
confidence: 99%
“…A suppression study of NLP6 demonstrated that this gene plays an important role in nitrate signaling and other NLP members are also speculated to have similar function (Konishi and Yanagisawa, 2013). Using systems biology, SPL9, TGA1, TGA4, AFB3, and NAC4 have been identified as nitrate regulators involved in early nitrate response signaling (Krouk et al, 2010b;Vidal et al, 2010Vidal et al, , 2013Alvarez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of molecular components involved in nitrate signaling have been identified to date in Arabidopsis. These include the nitrate sensor AtNPF6.3/ NRT1.1 (Ho et al, 2009), the CBL-INTERACTING PROTEIN KINASEs AtCIPK8 and AtCIPK23 (Ho et al, 2009;Hu et al, 2009), the RWP-RK TF NIN LIKE PROTEIN7 (AtNLP7; Castaings et al, 2009;Marchive et al, 2013), the LATERAL ORGAN BOUNDARY DOMAIN (LBD) gene family of TFs (AtLBD37, AtLBD38, and AtLBD39; Rubin et al, 2009), the auxin receptor AtAFB3 and its target AtNAC4 (Vidal et al, 2013), the TF TEOSINTE BRANCHED1/CYCLOIDEA/ PROLIFERATING CELL FACTOR1-20 (Guan et al, 2014), and the TGACG motif-binding factors AtTGA1 and AtTGA4 (Alvarez et al, 2014). However, nitrate signaling is not understood well in cereal crops such as wheat, rice, and maize, which are the most important food crops in the world.…”
Section: Tanac2 Belongs To a Cereal-specific Clade Of Nac Proteinsmentioning
confidence: 99%